Effect of directional loading on mechanical performance of HDPE warp knitted mesh fabric (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
This study examines the mechanical properties of high-density polyethylene (HDPE) warp-knitted mesh fabrics under varying directional loads. Four distinct fabric structures have been produced using different lapping plans on a tricot warp knitting machine, with each structure tested under three directional loads (0°, 45°, and 90°). The findings show a significant improvement in breaking strength in the wales (0) direction as compared to those in other fabric directions (45, 90) in all the fabric structures. Also, closed loop warp knit structure (S4) has greater bursting strength than the other samples due to its maximum stitch density.